Virus removal from bioproducts using ultrafiltration membranes modified with latex particle pretreatment. - Bellara, SR; Cui, Z; MacDonald, S; Pepper, D (1998)
Ultrafiltration is an attractive process for virus removal from bioproducts owing to its high throughput as well as the fact that the operation is carried out under ambient conditions (damage to proteins is highly limited). The principal concern regarding the adoption of conventional ultrafiltration membranes for virus removal is the possibility of the virus passing through abnormally large pores or surface imperfections on the membrane surface. The chief principle behind the present work is to pretreat the membrane by blocking the abnormally large pores using latex particles. Experimental work was conducted to validate this pretreatment using the bacteriophage phi x 174 as a model virus. The results attained were highly encouraging. Different sizes of latex particles were tested by treating a 100 KD molecular weight cut-off membrane, and the transmission of phage (suspended in buffer) through this membrane assessed. In the absence of any particle pretreatment, a virus clearance of 4.78 log reduction value was observed for this membrane. The transmission of phage through the membrane could be reduced by an order of magnitude using 0.11 micron latex particles, or two orders of magnitude using a combination of 0.11 and 0.50 micron particles. The application of latex particles did not hinder the transport of protein through the 100 KD membrane. Protein sieving coefficients obtained using this membrane were 91%, 16% and 2%, for lysozyme, HSA and IgG, respectively.